KINERJA KARYAWAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Anies Khaqul Yaqinah; Aprih Santoso (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
The problem in this research is that the Semarang Branch Mas telemarketing employees were unable to achieve the targets set by the Semarang Branch Sinar Mas Bank and this study aimed to analyze the factors of work ethic, skills, competence and communication towards the performance of telemarketing employees of Bank Sinar Mas Semarang Branch . The population in this study were all employees of the Semarang Branch SinarMas telemarketing, amounting to 66 employees while the sampling technique used was census technique and the analysis tool used in this study was multiple linear regression.The results showed that the work ethic, skills, competencies and communication variables had a positive and significant effect on the performance of the employees of Bank Sinar Mas Semarang Branch telemarketing and the results of the adjusted R square value in the regression model were obtained at 0.551 which means 55.1 percent of employee performance variables can be explained by work ethic, skills, competence and communication variables while the remaining 44.9 percent is explained by other variables outside of this study.